Food Safety of Animal Products That Viewed from Disease Aspect - ., Supar; Ariyanti, Tati (Indonesian Animal Sciences Society, 2005)
Animal diseases are tnajor factors affecting food producing anitnals at husbandry productions. The infectious and or non infectious diseases can influence the food quality of animal products and their safety for human consumption. The food safety of animal products becomes a world trade issue because it affects some aspects of human life quality and health. The food safety of anitnal products is defined at least by physical and health conditions of animal at preharvest period . It can be achieved by good manufacturing practice, beginning at animal production level up to the harvesting period. During this period, the animals must be protected against infection by pathogens of either bacteria, viruses or protozoa. linportant animal diseases which often cause problems during animal husbandry productions are anthrax, salmonellosis, brucellosis, tuberculosis, clostridiosis. colibacillosis, staphylococcosis. Some of the pathogens causing those diseases may also cause food poisoning and foodborne disease. The viral disease infection can affect food-safety at preharvest time but not at postharvest. At prcharvest period in fanns the disease can be controlled by vaccines and selected drug application. To obtain the good quality assurance of food producing animals and the safety for human consumption, the physical and the health conditions of animals can be determined visually. To determine the health status of food producing animals, each animal must be tested for the presence of pathogens and or specific antibody. This needs a veterinary laboratory facility with good equipments, chemical and diagnostic reagents. On the other hand, in order to pursue the good quality assurance of food producing animals up to the harvesting period, the hazard analysis critical control point (HACCP) and good agricultural practice (GAP) concepts in animal husbandry productions must be followed. Key words: Animal products, preharvest, human consumption, food safety